The disaster artist [videorecording (DVD)] : based on a true story - Franco, James, 1978-; Rogen, Seth, 1982-; Franco, Dave, 1985-; Apatow, Judd, 1967-; Sestero, Greg, 1978- (Lions Gate Entertainment, 2018)
The true-story of aspiring filmmaker and infamous Hollywood outsider Tommy Wiseau and a celebration of friendship and dreams pursued against insurmountable odds. When Greg Sestero, an aspiring film actor, meets the weird and mysterious Tommy Wiseau in an acting class, they form a unique friendship and travel to Hollywood to make their dreams come true. Based on the best-selling tell-all about the making of Tommy's cult-classic disasterpiece The Room.